(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2025)
Father involvement is one of many aspects that play an essential role in the development of children. Father involvement plays an important role, such as in morality education, discipline, independence, self-worth, and confidence. In Madurese, a father is one of the respected people in the family. Therefore, the involvement of Madurese fathers in taking care of their children will affect their children’s character development. The construct of this research is father involvement, with five dimensions, namely positive activity engagement, warmth and responsiveness, control, indirect care, and process responsibility. This research aims to describe the Madurese father’s involvement in the care of 6-12-year-old children qualitatively, using descriptive ethnography. The participant of this research is a Madurese father with a child aged 6-12 years old. The data has been collected through interviews and using the thematic analysis method. The result of this research showed that the five participants showed the five dimensions of father involvement. The most prominent dimension is control. Besides that, one characteristic that Madurese fathers show is that they do not like it when their family is disturbed by other people. It’s because Madurese fathers saw their family dignity as part of their self-worth. It has also been instilled from an early age.